Qoheleth and His Contradictions - Fox, Michael V. (Sheffield, Almond Press, 1989)
Fox takes as his starting point the issues that Quoheleth's interpreters have faced in their efforts to render the book faithfully, and in so doing, provides a new analysis of Quoheleth's reasoning, logic, and means of expression. Fox reaches three key conclusions about the work: Quoheleth is primarily concerned with the rationality of existence; Quoheleth is not against wisdom or the wise, and finally: Quoheleth supports the grasping of inner experience as the one domain of human freedom. These conclusions are supported by a thorough look at other analyses of Quoheleth
Keywords: Bible. -- O.T. -- Ecclesiastes; Theory of Knowledge